2014
DOI: 10.1021/jp500316s
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Structure, Backbone Dynamics, and Structural Topology of Phospholamban and Its Phosphorylated and Arg9Cys-Mutated Forms in Phospholipid Bilayers Utilizing 13C and 15N Solid-State NMR Spectroscopy

Abstract: Phospholamban (PLB) is a membrane protein that regulates heart muscle relaxation rates via interactions with the sarcoplasmic reticulum Ca2+ ATPase (SERCA). When PLB is phosphorylated or Arg9Cys (R9C) is mutated, inhibition of SERCA is relieved. 13C and 15N solid-state NMR spectroscopy is utilized to investigate conformational changes of PLB upon phosphorylation and R9C mutation. 13C=O NMR spectra of the cytoplasmic domain reveal two α-helical structural components with population changes upon phosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…Proposed mechanisms include trapping of PKA (8), disruption of PLB phosphorylation (8,9,20,21), and loss of PLB inhibitory function (8, 9, 20 -22). Other studies have suggested that the R9C mutation mimics PLB phosphorylation by partial unfolding of the cytoplasmic helix resulting in decreased helical conformation (23) or detachment of PLB cytoplasmic domain from the membrane surface (24,25). Moreover, we have previ-ously proposed that the R9C mutation induces oxidation-dependent cross-linking of adjacent R9C-PLB protomers (20).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Proposed mechanisms include trapping of PKA (8), disruption of PLB phosphorylation (8,9,20,21), and loss of PLB inhibitory function (8, 9, 20 -22). Other studies have suggested that the R9C mutation mimics PLB phosphorylation by partial unfolding of the cytoplasmic helix resulting in decreased helical conformation (23) or detachment of PLB cytoplasmic domain from the membrane surface (24,25). Moreover, we have previ-ously proposed that the R9C mutation induces oxidation-dependent cross-linking of adjacent R9C-PLB protomers (20).…”
mentioning
confidence: 78%
“…A, schematic representation of primary sequence of WT-PLB and the mutant PLB constructs. The amino acid sequence of the PLB protomer shows the N-terminal cytosolic domain Ia (residues 1-16), flexible linker (residues 17-22), domain Ib (residues [23][24][25][26][27][28][29][30], and the C-terminal transmembrane domain II (residues 31-52). Cer or YFP was fused to the N terminus.…”
Section: R9c-plb Exerts a Positive Inotropic And Positive Lusitropicmentioning
confidence: 99%
“…13 C solid-state NMR studies have shown that it is a hydrophobic α-helix that is aligned with domain II (Yu and Lorigan 2014). Upon S16 phosphorylation, domain Ib changes its structure from an α-helix to an uncoiled coil and loses its alignment with domain II (Yu and Lorigan 2014).…”
Section: Structural Dynamics Of Plb and Plb/serca2amentioning
confidence: 99%
“…13 C solid-state NMR studies have shown that it is a hydrophobic α-helix that is aligned with domain II (Yu and Lorigan 2014). Upon S16 phosphorylation, domain Ib changes its structure from an α-helix to an uncoiled coil and loses its alignment with domain II (Yu and Lorigan 2014). Alanine scanning of a peptide containing PLB residues 21-30 revealed that domain Ib residues N27 (which is K27 in humans), and N30 were also important for SERCA2a binding (Asahi et al 2001).…”
Section: Structural Dynamics Of Plb and Plb/serca2amentioning
confidence: 99%
See 1 more Smart Citation